Understanding the Effects of Cardamom Cultivation on Its Local Environment Using Novel Systems Thinking Approach-the Case of Indian Cardamom Hills - Murugan, Muthusamy; Ashokkumar, Kaliyaperumal; Alagupalamuthirsolai, M.; Anandhi, Aavudai; Ravi, Raju; Dhanya, M. K.; Sathyan, Thiravidamani (Frontiers in Sustainable Food Systems, 2022)
Intensive cardamom cultivation in Indian Cardamom hills (ICH) has been related to severe ecological and environmental implications that can challenge the long-term sustainability of cardamom. This research study and analysis proposes a novel system approach for sustainable agroecological production of cardamom in southern India. The effects of intensive cardamom cultivation on its forest environment had been significant. A considerable increase in surface air temperature was observed in the ICH during the last three decades (1990–2020). The climate of the Cardamom hill reserves (CHR) has a very high variability of daily cycles (surface air temperature and relative humidity) compared to low variability of yearly cycles, which helped minor and major pests and diseases occur and spread throughout the season. The current hydrothermal condition of the soil fostered the occurrence of soil insect pests, resulting in higher pesticide use. Epiphytes peculiar to the CHR forest have been eliminated due to repeated, intense shade lopping of each tree. Variability occurred in cardamom growth and development and yield can be attributed to changes in the microclimatic environment prevailing in the micro habitats of the sloping hillsides. This study has revealed the possible link and various dimensions between the intensive growing practices that were positively reflected in its local climate and production system. The 75% shade level under the cardamom canopy influences the cardamom microclimatic conditions, the relative humidity close proximity with panicles was maximum (88.9%), and the mean air temperature was minimum (18.4°C). On the contrary, the relative humidity at canopy top was reduced (78.7%) but the mean air temperature was still high (27.4°C). This study also suggests that future energy transfers in the CHR production system must be understood for improving the long-term agricultural sustainability of cardamom cultivation in the ICH.